Transition of the quality management system to the aviation safety management system in organizations dealing with base aircraft maintenance - Babić, Roman; Kacian, Irina; Špehar, Dominik (Crisis Management Days, 2024)
The paper deals with the transition from the quality management system to the aviation safety management system in organizations dealing with aircraft maintenance. For all activities and changes in an organization, the risk of endangering flight safety is assessed and preventive activities are determined according to the risk category. The transition to the aviation safety system is based on the requirements stated within ICAO Annex 19 document - Safety Management System. EU regulatory norms (including the EASA norm that describes organizations for basic technical maintenance of aircraft - Part 145 norm) require organizations to comply with new regulatory requirements by the beginning of December 2024. The transition includes comprehensive organizational, documentation and procedural changes in organizations and is essentially deregulatory in nature, increasing the responsibility of management structures in organizations for the outcomes of technological activities affecting flight safety (safe use of aircraft).